Pemahaman Jemaat GBI AM terhadap Doktrin Kasih Karunia dan Relevansinya terhadap Pertumbuhan Rohani dalam perspektif Teologi Reformed-Injili (Studi berdasarkan Efesus 2:1-10 dan Roma 5:1-11) - Rasmalem Raya Sembiring; Robbye Manik; Aslinawati; Petrus Posma Silaban (Sekolah Tinggi Teologi Sola Gratia Medan, 2025)
Abstract This study aims to describe the GBI Antiokhia Medan congregation's understanding of the doctrine of God's grace and examine how this understanding is relevant to their spiritual growth. This study employed a qualitative, descriptive-phenomenological approach through in-depth interviews with several GBI AM congregation members. Two biblical texts form the the theological foundation of the study : Ephesians 2:1-10 and Romans 5:1-11, which emphasize that salvation is received solely by God’s grace. The findings indicate that, in general, the congregation understands grace as an undeserved gift from God. However, some members still tend to associate it with human efforts to